Pengaruh Perbedaan Pre-Treatment terhadap Stabilitas Karotenoid dan Fenol pada Ekstrak Sargassum duplicatum selama Penyimpanan: The effect of different pre-treatments on carotenoid and phenol stability of Sargassum duplicatum methanol extract during storage - Dita Wardani, Ayunda; Susanto, Eko; Nurcahya Dewi, Eko; Purnamayati, Lukita (Jurnal Pengolahan Hasil Perikanan Indonesia, 2020)
Carotenoids and phenols are compounds contained in seaweed that possessed free radical scavenging activities. However, both compounds showed lower stability. The temperature treatments may affect the stability of both compounds. The aimed of this study was to determine the effect different pre-treatment blanching (high temperature) and freezing (low temperature) to maintain their stability in methanol extract of Sargassum duplicatum during storage at room temperature. The research method used was experimental laboratories using the basic design of a Completely Randomized Design (CRD) with a factorial pattern of 2 x 5 which divided into processing temperature factors (high temperature and low temperature) and storage time (0, 2, 4, 6, and 8 day). Blanching was carried out at a 95oC while freezing at -27oC. The results showed that carotenoids, fucoxantin, and phenol compounds with blanching treatment were more stable than freezing treatments. This study showed that blanching treatment was effectively retard the degradation of carotenoids, fucoxanthin, phenol content during room temperature storage. Keywords: Blanching, Fucoxanthin, Carotenoids, Phenol